The Sea Power of Small States: A Case Study of Sri Lanka - Kumara, Jeewaka Saman (European Scientific Journal, ESJ, 2021)
The geo-strategic location of Sri Lanka in the Indian Ocean, which is a part of global and regional power competition, is close to the key and busy naval routes between the East and the West. Particularly, the marine area of Sri Lanka has critical geopolitical importance due to its location between the Strait of Hormuz and the Strait of Malacca, which are essential transit zones in the world. The marine area of Sri Lanka has gained much attention from the industrial and newly industrial nations due to the living and non-living natural resources contained in the surrounding sea. With this background note, this paper focuses on discussing the sea power dimension of national security, focusing on the case of Sri Lanka, which has been neglected by contemporary academia of small powers’ studies. For this purpose, Alfred Thayer Mahan’s theory on sea power has been employed to theoretically and practically examine the feasibility of its application for enhancing the sea power of Sri Lanka in the context of changing global order. The research was drawn from a wide range of secondary sources and a descriptive analysis was made. The paper concludes with implications for some realistic policies for enhancing the sea power capacity of Sri Lanka as it allows the free flow of people and goods as well as the projection of naval power of Sri Lanka.